Evolution of Helicobacter pylori associated with gastroduodenal ulcers or erosions in children over the past 23 years: Decline or steady state?. Issue 5 (8th July 2019) - Burgard, Marie; Kotilea, Kallirroi; Mekhael, Joyce; Miendje‐Deyi, Veronique Yvette; De Prez, Carine; Vanderpas, Jean; Cadranel, Samy; Bontems, Patrick
Abstract: Background: Recent data suggest that in children, the proportion of gastroduodenal ulcers/erosions associated with Helicobacter pylori infection is currently lower than expected. In this study, we trace this proportion over two decades. Methods: We reviewed the reports of all upper gastrointestinal endoscopies with biopsies for histology and culture over the past 23 years. H pylori status was assessed using several invasive methods. The infection rate during different time periods was compared between children with lesions and controls. Results: A total of 7849 endoscopies were performed in 5983 children (2874 F/3109 M, median age 7.6 years, range 0.1‐17.9 years). The endoscopy report was missing in 316 patients. At the first upper gastrointestinal endoscopy, 12.1% of the children presented with gastric and/or duodenal ulcers or erosions with an H pylori infection rate of 35.4%, whereas no such lesions were observed in 87.9% of children in whom the H pylori infection rate was 21.3%. The risk factors associated with such lesions were older age ( P  < 0.001), male sex ( P  = 0.002), and H pylori infection ( P  < 0.0001). Gastric ulcers were not significantly associated with H pylori (24% infected), whereas 52% of duodenal ulcers, 33% of gastric erosions, and 38% of duodenal erosions were associated with H pylori. The proportion of gastroduodenal lesions associated with H pylori remained stable over time. Children with H pylori infection and ulcers were older than those with H pylori infection without ulcers ( P  < 0.001). Conclusions: Our study indicates that in our pediatric population, the proportion of ulcers without H pylori infection is higher than previously suggested, and this prevalence has not changed over the past two decades.